Impact of the Mediterranean Economic Growth on the European Port and Transport System - Musso, Enrico; Ferrari, Claudio (Promet - Traffic&Transportation, 2012)
The Mediterranean Countries (MC) are grouped as EuropeanUnion Countries (EUC), Former Socialist Countries(FSC), Middle East Countries (MEC) and Maghreb Countries(MAC) and their economic and population prospects are analysedwith respect to future demands on seaborne traffic, portcapacity and hinterland relations in the 21' century.